2008
DOI: 10.2134/agronj2007.0198
|View full text |Cite
|
Sign up to set email alerts
|

Hard Red Spring Wheat Response to Row Spacing, Seeding Rate, and Nitrogen

Abstract: Row spacing, plant density, and N application timing can be manipulated to optimize plant growth and spatial distribution, therefore maximizing sunlight, nutrients, soil water use effi ciency and grain yield. A 2-yr fi eld study to evaluate the eff ects of four seeding rates (108, 215, 323, and 430 seeds m -2 ), two row spacings (15 and 30 cm), and three N treatments (FA1, 100% at seeding; FA2, 50% at seeding and 50% at tiller formation; and FA3, 50% at seeding and 50% at shoot elongation) on grain yield of Mc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 40 publications
6
70
0
Order By: Relevance
“…In Washington State, USA, Schillinger (2005) found no effect of seeding rate on grain yield of wheat, oats and barley, with seeding rates of 120, 200 and 280 grains m (2 . In contrast, in semiarid regions, Chen et al (2008) observed an increase in wheat yield from 180 to 215 grains m (2 , which can be explained by insufficient water resources for plants to compensate for low populations. They did not find any subsequent yield increase from 215 to 430 grains m (2 .…”
Section: Results and Discussion Yields And Agronomic Measurementsmentioning
confidence: 86%
“…In Washington State, USA, Schillinger (2005) found no effect of seeding rate on grain yield of wheat, oats and barley, with seeding rates of 120, 200 and 280 grains m (2 . In contrast, in semiarid regions, Chen et al (2008) observed an increase in wheat yield from 180 to 215 grains m (2 , which can be explained by insufficient water resources for plants to compensate for low populations. They did not find any subsequent yield increase from 215 to 430 grains m (2 .…”
Section: Results and Discussion Yields And Agronomic Measurementsmentioning
confidence: 86%
“…In modern agriculture, field crops, especially the cereals, are planted in distinct rows with variable row spacing and plant densities (Chen et al, 2008). Manipulation of crop row spacing and its orientation has been suggested as a mean to reduce light interception by weeds (Chauhan, 2012).…”
mentioning
confidence: 99%
“…For example, Sweeney & Sisson (1988) reported 15 % wheat grain yield increases in a bed planting system compared to yield obtained in the 'flat' indicating that other factors such as rainfall patterns may be accounting for the differences between systems. The higher yield from beds can be attributed to greater resource utilization through the changes in row spacing and plant density configuration (Chen et al, 2008). It is well known that wheat plants in narrow-raised beds can compensate, within certain limits, for the lost cropping areas of the open furrows between beds.…”
Section: Variations Due To Topological Arrangement Of Small Grain Cermentioning
confidence: 99%
“…In this case, variety Nahuatl F2000 was the most stable across environments probably due to its tillering ability. Yield components that determine wheat grain yield are heads per m 2 , heads per plant, kernels per head and kernel weight and there are compensatory relations among them in response to the changes of environmental conditions and agronomic practices, such as row spacing and seeding rate (Chen et al, 2008). Research work has shown a consistent relationship between grain yield and number of heads; the former increases as the latter improves (Zhang et al, 2007;Chen et al, 2008).…”
Section: Varietymentioning
confidence: 99%